Laparoscopic versus open cystgastrostomy for pancreatic pseudocysts: a case‐matched comparative study. (31st July 2014) - Khaled, Yazan S.; Malde, Deep J.; Packer, Jessica; Fox, Thomas; Laftsidis, Prodromos; Ajala‐Agbo, Tolulope; De Liguori Carino, Nicola; Deshpande, Rahul; O'Reilly, Derek A.; Sherlock, David J.; Ammori, Basil J.
Abstract Background Cystgastrostomy is the commonest method of internal drainage of pancreatic pseudocysts (PPs). While large and persistent retrogastric pancreatic pseudocysts are amenable to laparoscopic cystgastrostomy, the potential benefits of this minimally invasive laparoscopic approach over open surgery remain to be demonstrated. The aim of this study was to compare the outcomes of the laparoscopic and open approaches for cystgastrostomy. Methods Patients who underwent laparoscopic cystgastrostomy (LCG) were matched on a 3:1 basis to those who underwent open cystgastrostomy (OCG) according to age, sex distribution, and size of pseudocyst. The outcomes of the two approaches were compared on an intention‐to‐treat basis. Data shown represent medians. Results A total of 54 patients underwent cystgastrostomy (35 LCG, 19 OCG) between 1997 and 2011. The final case matched cohort consisted of 40 patients (12 female and 28 male) of which 30 underwent LCG (two converted to open surgery) and 10 underwent OCG. The laparoscopic and open groups were comparable for age (55 vs. 59 years, P = 0.80), sex distribution, and size of pseudocyst (10 vs. 13 cm, P = 0.51). The laparoscopic approach had a significantly shorter operating time (62 vs. 95 min, P = 0.035) and carried a significantly lower risk of postoperative morbidity (10% vs. 60%, P = 0.024) and shorter postoperative hospital stay (6.2 vs. 11 days, P = 0.038). There was one operative death after OCG (10%). Conclusion The laparoscopic approach to cystgastrostomy for large and persistent retrogastric pancreatic pseudocysts is associated with a shorter operating time, smoother and more rapid recovery, and a shorter hospital stay compared with open surgery. The laparoscopic approach should be considered the preferable approach where expertise is available.